Tracing representations of deviant masculinity in selected eighteenth-century English novels - Ismail, Hanita Hanim (2017)
To date, there is an evident insufficiency and neglect in the current scholarship of masculinity, particularly the deviant masculinity as depicted in eighteenth-century novels which only provides an unrepresented perception of the gender. This thesis problematizes such neglect, hoping that an examination on men’s power-relations across and between gender as exhibited by the selected deviant men, namely The Prince and The Jew from Daniel Defoe’s Roxana (1724), Mr. Robert of Samuel Richardson’s Pamela (1740), Mr. Lovelace of Clarissa (1747), Ephraim Jenkinson from Oliver Goldsmith’s Vicar of Wakefield (1766) and Tom Jones from Henry Fielding’s Tom Jones (1749) will provide insights on deviant masculinity and enable a postulation of a probable correlation between the use of power-relation at establishing masculinity and the role of socio-political conditions, particularly its given space. I propose the use of Foucault’s genealogical approach at examining and problematizing power-relations, particularly by these men in order to trace deviant masculinity and its mechanics. I also intend on using Foucault’s ‘heterotopia’ in order to understand the empowering of deviant masculinity. Each analysis chapter will examine and problematize targeted deviant typology. It is interesting to observe a variation of power technologies used by the deviant men between and across genders, which show their extended level of intelligence at manipulating power, be it social or political-wise, to their advantage.